Use of Malaysian English discourse particles in facebook among Chinese Malaysian youth - Tay, Li Chia (2014)
The informal variety of English spoken by a large section of society in Malaysia is known as Malaysian English (ME). ME is generally believed to have evolved partly due to the multi-ethnic and multi-lingual composition of Malaysian society as evidenced by the many words and particles from the local languages incorporated into the variety of English that is not considered to be the standard form. This study seeks to examine the use of discourse particles (DPs) among Chinese Malaysian youth in the context of computer-mediated communication. It aims to investigate the types and frequencies of the DPs used and their pragmatic functions. This study also examines differences in DP use by the Chinese Malaysian youth with that by Singaporeans, taking the study of DPs in Singaporean English by Low and Brown (2005) as the basis for the comparison. The data for the present study consists of 200 Facebook conversations obtained from the wall posts of twenty Chinese Malaysian youth. Ten male and ten female Facebook profile owners and 200 conversations containing DPs were selected through purposive and quota sampling methods. This study is located within the pragmatic framework and the data are analysed using the typology and scheme of DP pragmatic functions adopted from Low and Brown (2005). In this study, the use of DPs appears to play important communicative functions in computer-mediated communication (CMC). The findings of the study reveal that the DPs ah, eh, hor, lah/ la, lor/ lo, ma/ mah, meh, what, leh, one, de, geh, o,wor, ke/kah, kan, wei, gua, bah, ya, and nah are used by young Chinese Malaysian Facebook users. The DPs lah/ la, lor/ lo and leh are the most frequently used DPs by Chinese Malaysian youth in their Facebook conversations. Besides that, ME DPs are multi-functional and convey attitudinal meanings such as to soften an order or an advice, to establish rapport, to express resignation, to point out what a speaker deems obvious, to express surprise or disbelief, to soften a warning and so on. It was found that DPs serves to indicate social distance,relationship and attitudes among the interlocutors. This study reveals that ME DPs are used systematically and understood by its speakers in the community. All the Singaporean English DPs from the DP framework by Low and Brown (2005) which are ah, eh, hor, la/ lah, lor, ma/ mah, meh, and what were also used by Chinese Malaysian youth in their conversations, and lah/ la is the most frequently used DP in Malaysia and Singapore. It is interesting to note that more types of DPs were found in the Malaysian data, probably due to a more diverse population in Malaysia. Further research could focus on comparing the use of DPs in face-toface and computer-mediated communication among Chinese Malaysian youth.